Cellular mechanisms of hormone secretion in neuroendocrine tumors: what goes wrong? - Streit, Laura; Tanguy, Emeline; Brunaud, Laurent; Tóth, Petra; Vitale, Nicolas; Ory, Stéphane; Gasman, Stéphane (Frontiers in Cell and Developmental Biology, 2025)
Neuroendocrine tumors (NETs) constitute a heterogeneous group of neoplasms arising from hormone-releasing cells. Secretion of hormones stored in vesicles occurs through calcium-regulated exocytosis, a process that needs to be tightly controlled to avoid unbalanced levels of hormones. A critical feature shared by most of the NETs is a dysfunctional secretory pathway mainly leading to hypersecretion, which often induces clinical complications. In this review, we focus on the cellular process of hormone exocytosis and discuss the potential molecular mechanisms leading to deregulated hormone secretion in various NETs. Particular attention is paid to expression level modifications for genes and proteins involved in the exocytic pathway in NETs.